Sosialisasi dan Pelatihan Optimalisasi Pemanfaatan Lahan Pekarangan Di Desa Karangrejo Kecamatan Loano Kabupaten Purworejo - Kurniawan, Kukuh (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The purpose of this service is to optimize food in an effort to utilize the yard as a planting medium for various kinds of vegetables. The location chosen was Karangrejo Village, Loano District, Purworejo Regency, Central Java. The implementation method used is counseling on the use of yard land, training on making planting media and plant racks, training on making organic fertilizer by utilizing household waste, and training on making husk charcoal. Through this activity, the community can make optimal use of their yards and harvest the results in the form of eggplants and chilies. The use of home yards can bring various benefits, such as a shop, pharmacy, living barn, and living bank.